2009
DOI: 10.3109/14764170903449752
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing after laser skin resurfacing: The effect of a silver sulfadiazine-hyaluronic acid-containing cream under an occlusive dressing

Abstract: The cream containing silver sulfadiazine/hyaluronic acid seems to improve wound healing after laser skin resurfacing in guinea pigs. The clinical application of this finding on humans should be assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Costagliola et al [38] showed that HA formulations were effective and well tolerated for the treatment of second-degree burns. It was also demonstrated that HA-based products could enhance healing following surgery or laser skin resurfacing [14,39]. Martini et al [40] investigated the effects of two different formulations of TVE (soaked gauzes and cream) in comparison to a gel form of equine catalase (Citrizan) for the topical treatment of small-to-medium-sized second-degree burns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Costagliola et al [38] showed that HA formulations were effective and well tolerated for the treatment of second-degree burns. It was also demonstrated that HA-based products could enhance healing following surgery or laser skin resurfacing [14,39]. Martini et al [40] investigated the effects of two different formulations of TVE (soaked gauzes and cream) in comparison to a gel form of equine catalase (Citrizan) for the topical treatment of small-to-medium-sized second-degree burns.…”
Section: Discussionmentioning
confidence: 99%
“…HA is involved in each phase of wound healing: it stimulates cell migration, differentiation, and proliferation; moreover, it regulates ECM organization and metabolism. HA was combined with silver sulfadiazine (SSD), which prevents colonization of the wound [14], to create an advanced dressing marketed under the brand name Connettivina ® Bio Plus gauzes and cream (Fidia Farmaceutici S.p.A., Abano Terme, Italy).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the scores of wound colonization were the lowest (2.2 in 1 st week) in silver treated animals (group S). Silver sulfadiazine increases the rate of reepithelialization in acute and chronic wounds and had good effects in wound healing (Kontoes et al, 2010;Choi et al, 2013). It may be suggested that, 1% silver sulfadiazine may be used as an effective topical medication for treating wounds in rabbits.…”
Section: A B D Cmentioning
confidence: 99%
“…Topical antibacterial therapy may alter the wound environment by reduction of fibroplasia or promotion of epithelialization (Stashak, 1991;Mashhood et al, 2006). Silver nitrate, Nano crystalline silver, and some silver-containing dressings have anti-inflammatory effects and encourage neovascularization (Walker et al, 2007;Kontoes et al, 2010;Wilkinson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[80][81][82][83][84][85][86][87][88] . Στον άνθρωπο έχει αποδειχθεί κλινικά η ευνοϊκή επίδραση του υαλουρονικού οξέος σε χρόνια τραύματα90- 94,96 και σε εγκαύματα95,96 .Αντίθετα, σε προηγούμενή μας μελέτη, η οποία περιελάμβανε μικρότερο δείγμα ασθενών και κλινική εκτίμηση των ουλών μόνο τη 10 η μετεγχειρητική ημέρα, είχαμε δείξει ότι το υαλουρονικό οξύ δε φαίνεται να επηρεάζει το κλινικό αποτέλεσμα της επούλωσης σε αυτή τη χρονική στιγμή136 .Στην παρούσα εργασία εξετάσαμε την επίδραση της τοπικής εφαρμογής κρέμας υαλουρονικού οξέος 0,2% στην επούλωση χειρουργικών τομών, σε σχέση με σκεύασμα όμοιας φαρμακοτεχνικής μορφής, το οποίο χρησιμοποιήθηκε ως μάρτυρας, και σε βάθοςχρόνου, εστιάζοντας στο κλινικό (αισθητικό) αποτέλεσμα της ουλοποίησης.…”
unclassified